Supervising the Use of Mother Tongue Language in K-12 Education: IP School in Focus - Malong, Jr, Camilo D; General, Lorna T (International Journal of Management Excellence (ISSN: 2292-1648), 2018)
The purpose of this phenomenological study was to investigate and analyze the supervision of the use of mother tongue language in K to 12 education in Caraga Davao Oriental. Employing phenomenological approach with 14 school heads, in-depth interview and focus group discussion were conducted which revealed that most of the participants’ experiences in supervising mother tongue were frustration with ineptitude, collateral complications, collaboration among teachers, improved student engagement, and compassionate intervention. The coping mechanisms of the participants include being keen and efficient, being scientific and methodical, being creative and resourceful, peer mentoring, and benchmarking. Despite the rigors of life, the respondents shared insights based on their experiences. These include MTB language promotes cultural preservation, teachers need steady support, and administrators need a helping hand. The study implies that their realization after supervising and upon implementing what they have learned, they were amazed of the transformation that happened to their teachers in particular and the schools in general.